2022
DOI: 10.1021/acsami.2c10171
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Suitable Solvent Additive for 2-Methoxyethanol-Based Antisolvent-Free Perovskite Film Fabrication

Abstract: In this study, we compare various solvents with different Gutmann donor numbers as additives to improve the quality of perovskite films via an antisolvent-free process, using 2-methoxyethanol (2MOE) as the solvent. In 2MOE-based solutions, we found that the higher the donor number of the solvent, the lower the amount of the solvent required to form insoluble adducts. Furthermore, we found that N-methyl-2-pyrrolidone (NMP), which has a relatively low donor number and vapor pressure, can be added without a limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The shallow trap states can be presented at the SnO 2 -NRs/perovskite interface. 23 In particular, the PL peak shows a small blue-shift after the addition of Cl-BSM, indicating the reduction of shallow trap states. In other words, the Cl-BSM can efficiently passivate the trap states at the SnO 2 -NRs/ perovskite interface.…”
Section: The Defect Density and Carrier Recombination Characterizatio...mentioning
confidence: 98%
See 1 more Smart Citation
“…The shallow trap states can be presented at the SnO 2 -NRs/perovskite interface. 23 In particular, the PL peak shows a small blue-shift after the addition of Cl-BSM, indicating the reduction of shallow trap states. In other words, the Cl-BSM can efficiently passivate the trap states at the SnO 2 -NRs/ perovskite interface.…”
Section: The Defect Density and Carrier Recombination Characterizatio...mentioning
confidence: 98%
“…20 Besides DMSO, 2-methoxyethanol (2-Me) with lower toxicity was also used to replace DMF in many large-area fabrication processes of PSCs. [21][22][23][24][25][26] Without strong coordination ability, 2-Me often requires other toxic solvent additives, such as acetonitrile (ACN) 22 and N-methylpyrrolidone (NMP), 23 to achieve a desirable film morphology and device performance. Recently, a new family of greener solvents, triethyl phosphate (TEP) and trimethyl phosphate (TMP), 27,28 show comparable dissolving ability for perovskite precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum PCE of 20.39% based on MAPbI 3−x Cl x film prepared from the 2MOE-based solution containing NMP without anti-solvent could be achieved. [22] Most of the studies on PSCs fabricated by anti-solvent free technology process are based on MAPbI 3 -typed perovskite materials, which often lead to poor photovoltaic device stability and limit further improvement of PCE due to volatility of MA component in perovskite under temperature >80 °C and relatively wider bandgap (1.60 eV). [23] Besides, almost all research works that are based on anti-solvent free spinning-coated technology focus on the coordination interaction between solvent molecules and perovskite components (PbI 2 or FAI) that is the prerequisite for the formation of perovskite intermediate phase, but the mechanism of the intermolecular interaction between primary solvent like N, N-Dimethylformamide (DMF) and co-solvent like DMSO or NMP on nucleation process and formation process of intermediate phase has hardly been concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several solo, binary, and ternary solvents have been introduced without DMF to prepare various compositions of green perovskite inks. [13,[15][16][17][18][19][20][21] Sun et al employed a mixture of methylammonium acetate and ACN to fabricate high-performance MAPbI x Br 3−x devices, in which the ACN minimized the coordination of the solvent and perovskite solutes that led to the formation of large micelles. [22] Cassella et al demonstrated up to 18.0% efficiency for the MAPbI 3 PSCs from a binary solvent of 2-ME and tetrahydrofuran.…”
Section: Introductionmentioning
confidence: 99%